Suggested Resources for Scholarly Teaching and for the Scholarship of Teaching and Learning - Craig E. Nelson (American Society for Microbiology, 2011)
These are some of my favorite resources of informing scholarly teaching (ST) and the scholarship of teaching and learning (SOTL). This list is focused on the needs of college biology faculty. It is highly selective and somewhat idiosyncratic in that many more items are relevant and could have been included.